Short-term Opportunities for International Collaboration Through the Fulbright Specialist Program - Amirah Nelson (Academic Chairpersons Conference Proceedings, 2022)
This presentation will provide insight on how established U.S. academics, administrators, and professionals can engage with a range of overseas institutions through the Fulbright Specialist Program, a part of the larger Fulbright Program that pairs highly qualified U.S. academics and professionals with host institutions abroad to serve as expert consultants and engage in a short-term (2- to 6-week long) project-based exchange.
Keywords: International Exchange; Faculty Professional Development; Fulbright